Safety evaluation of medroxyprogesterone acetate: a pharmacovigilance analysis using FDA adverse event reporting system data - Su, Luyang; Xu, Ren; Ren, Yanan; Zhao, Shixia; Liu, Weilan; Du, Zeqing (Frontiers in Pharmacology, 2024)
Background Medroxyprogesterone acetate (MPA), a synthetic progestogen, is extensively used for the treatment of various conditions, including contraception, irregular menstruation, functional uterine bleeding, and endometriosis. However, like all pharmaceutical agents, MPA is associated with adverse drug reactions. This study aimed to evaluate the adverse events (AEs) associated with MPA in by analyzing real-world data from the U.S. Food and Drug Administration’s Adverse Event Reporting System (FAERS). By providing a comprehensive assessment of the safety profile of MPA, this study seeks to support informed clinical decision-making. Methods Data covering the period from the first quarter of 2004 to the first quarter of 2024 were collected from the FAERS database. Disproportionality analyses were conducted using several statistical methods, including reporting odds ratio (ROR), proportional reporting ratio (PRR), empirical Bayesian geometric mean (EBGM). Additionally, time-to-onset (TTO) analysis was employed to quantify the signals of the MPA-associated AEs. Results A comprehensive dataset comprising 21,035,995 AE reports was compiled. Among these, 3,939 women reported using MPA as a contraceptive method. The reports covered 27 system organ classes (SOCs) and 25 high-frequency AE signals. Notably, significant AEs were identified, some of which were not previously detailed in the medication’s prescribing information. Unforeseen significant AEs such as unintended pregnancy (n = 623; ROR, 6.65; ROR025, 6.1; χ2, 2,482.38; PRR, 6.41; EBGM, 5.69; EBGM05, 5.29), bone pain (n = 35; ROR, 13.78; ROR025, 9.4; χ2, 311.2; PRR, 13.75; EBGM, 10.59; EBGM05, 7.69), gait disturbance (n = 34; ROR, 2.82; ROR025, 1.99; χ2, 37.31; PRR, 2.88; EBGM, 2.7; EBGM05, 2.02), dental caries (n = 15; ROR, 23.16; ROR025, 12.32; χ2, 204.26; PRR, 23.14; EBGM, 15.23; EBGM05, 8.98), decrease in blood pressure (n = 15; ROR, 3.88; ROR025, 2.29; χ2, 29.35; PRR, 3.88; EBGM, 3.63; EBGM05, 2.33), and osteonecrosis (n = 9; ROR, 23.44; ROR025, 10.36; χ2, 123.67; PRR, 23.43; EBGM, 15.35; EBGM05, 7.75) were identified as AEs that were not previously outlined in the prescribing information of the medication. Conclusion Our findings align with clinical observations, highlighting the emergence of previously unreported AE signals associated with MPA and their demographic and TTO characteristics. Further pharmaco-epidemiological studies are required to substantiate these observations.